THE DIVERSITY AND CHARACTERISATION OF CELLULOLYTIC BACTERIA ISOLATED FROM VARIOUS CONDITIONS OF EMPTY FRUIT BUNCHES IN OIL PALM PLANTATION - Agam Pamungkas, Edo; Madusari, Sylvia; Putri, Halida Adistya; Rosita, Risa (BRIN - Badan Riset dan Inovasi Nasional, 2025)
The utilisation of oil palm empty fruit bunches (EFB) remains underexplored. Harnessing cellulolytic microorganisms for the production of cellulase enzymes offers sustainable approach to addressing waste management challenges while aligning with the principles of the Sustainable Development Goals (SDGs) and address waste management challenges. This study aims to isolate, characterize, identify, and test the potential cellulase activity of cellulolytic bacteria from EFB taken from three different locations: PO code from organic fertilizer plantations (POU1, POU2, POU3), PL code from oil palm plantations (PLU1, PLU2, PLU3), and PK code from Sulung mills (PKU1, PKU2, PKU3). This study used three isolated cultures in its testing. The research process includes sample preparation, bacterial isolation, gram staining, catalase test, hypersensitivity test, DNA amplification, bioinformatics analysis and cellulase activity analysis. The results of the bacterial isolation obtained 28 colonies. The results of the characterisation were all 3 non-pathogenic bacterial isolates, with a positive catalase test. The result of staining Gram-negative with bacilli-shaped bacteria. The amplification results obtained a band size of 1500 bp. The results of the identification obtained the species Aeromonas enteropelogenes, Nitrosomonas stercoris, and Methylobacillus caricis. The results of phylogenetic analysis showed low homology. Cellulase activity of six positive isolates with medium ability isolates code POU3 (1.3), PLU2 (1.0), PLU3 (1.0); low isolates POU1 (0.2), POU2 (0.2), PLU (0.8) and 3 negative isolates no enzyme activity PKU1 (-1), PKU2 (-1), and PKU3 (-1).